A proteção da fauna silvestre nas propriedades privadas - Melo, Marcelo Augusto Santana de (2022)
The motivation of this work was the investigation of the problem related to the protection of fauna and private real estate properties. The intense and inseparable union that exists between life and its physical support (forest or vegetation) results in the fact that the protection of flora and fauna must be studied from the perspective of their respective territory. Thus, the genesis of the methodology is the study of property (Chapter 1), since, as a real right par excellence, it configures the axis around which the right of things gravitates and must serve a social function that comprises the environmental aspect with respect the protection of flora and fauna. In sequence, Environmental Law was studied (Chapter 2) to understand the connection between fauna and property, entering the main principles applied to the proposed problem; and then, due to the inseparable connection between environmental protection and Science in the determination of hazards, risk assessment, protection and ecological function, the influence for the Law as a subsystem and, in this aspect, that is, for the understanding of the essential communication between Science and Law The study focused on Luhmann's systems theory (Chapter 3). As a result, an attempt was made to delimit the concept of wild fauna, as well as to analyze the degrees of protection they receive, especially in relation to endangered or endangered species (Chapter 4). Because the habitats of wild species are protected, by environmental law, by environmentally protected spaces, these were scrutinized, especially those inherent to private areas. However, the protection of wild fauna in other countries where private property ownership has an essential functional aspect for the protection of nature was also analyzed (Chapter 5). Finally, aiming to understand the need for communicative symmetry between Science and Law, the inquiry focused on theoretical investigation of the resolution of fauna protection on private properties in accordance with current legislation and verification of the absence of an adequate standard for the protection of endangered wildlife, with a suggestion by lege ferenda (Chapter 6)